Facilitating Collective Psychosocial Resilience in the Public in Emergencies: Twelve Recommendations Based on the Social Identity Approach - Drury, John; Carter, Holly; Cocking, Chris; Ntontis, Evangelos; Tekin Guven, Selin; Amlôt, Richard (Frontiers in Public Health, 2019)
Accumulated evidence demonstrates the centrality of social psychology to the behaviour of members of the public as immediate responders in emergencies. Such public behaviour is a function of social psychological processes – in particular identities and norms. In addition, what the authorities and relevant professional groups assume about the social psychology of people in emergencies shapes policy and practice in preparedness, response and recovery, which in turn has consequences for the public’s ability to act as immediate responders. In this Policy and Practice Review, we will do three things. First, we will overview research on the behaviour of survivors of emergencies and disasters, drawing out key factors known to explain the extent to which survivors cooperate in these events and contribute to safe collective outcomes. We will demonstrate the utility of the social identity approach as an overarching framework for the major mechanisms of collective supportive behaviour among survivors in emergencies. Second, we will critically review recent and current UK government agency guidance on emergency response, focusing particularly on what is stated about the role of survivors in emergencies and disasters. This review will suggest that the “community resilience” agenda has only been partly realised in practice, but that the social identity approach is progressing this. Third, we will derive from the research literature and from dialogue with groups involved in emergencies a set of 12 recommendations for both emergency managers and members of the public affected by emergencies and disasters. These focus on the crucial need to build shared identity and to communicate, and the connection between these two aims. Including our recommendations within emergency guidance and training will facilitate collective resilience, which refers to the way a shared identity allows groups of survivors to express and expect solidarity and cohesion, and thereby to coordinate and draw upon collective sources of support. In sum, this evidence-base and the recommendations we derive from it will help professionals involved in emergency management to support public resilient behaviours and will help the public to develop and maintain their own capacity for such resilience.